Diseño y Simulación de un intercambiador de calor de tubos y coraza en el software solidwork. (2020)
From the bibliography consulted, a tube and shell heat exchanger is designed and simulated, with one step through the shell and two steps through the tubes, which presents a type of parallel and countercurrent flow, according to TEMA Standards (Tubular Exchanger Manufacturers Association), where the fluids involved are: water (cooler) for the absorption of heat inside the tubes and a carrier heat fluid such as water at high temperature by the shell, rejecting heat by convection and conduction, resulting in the transfer of energy (heat) to the fluid of lower temperature, without coming into contact with each other. This equipment is destined to form part of the Thermodynamics Laboratory as didactic support for the FIMEB Engineering Faculty.